Lung function, breathing pattern, and gas exchange in interstitial lung disease. Issue 2 (February 1992) - Javaheri, S; Sicilian, L
Abstract : BACKGROUND: The aim of this study was to determine the relation between the severity of abnormalities in ventilatory function tests and tidal breathing pattern and gas exchange indices in interstitial lung disease. METHODS: Pulmonary function, ventilation, carbon dioxide production, oxygen consumption, arterial blood gas tensions, and pH were measured during resting steady state conditions in 60 patients with proved interstitial lung disease. Patients were categorised by forced vital capacity (FVC) (percentage of predicted values) as having a mild, moderate, or severe restrictive defect with means (SD) of 71% (4%), 57% (4%), and 41% (7%) of predicted values, respectively. RESULTS: FVC varied from 29% to 79% of predicted values and from 0.99 l to 4.32 l. The two measurements of FVC correlated strongly with most static lung volumes and with transfer factor for carbon monoxide. Mean respiratory rates (per minute) and tidal volumes (ml) were 17 (4) and 484 (131), 20 (4) and 460 (139), and 23 (5) and 377 (109) in mild, moderate, and severe restrictive defects, respectively. FVC correlated negatively with respiratory rate and positively with tidal volume. Arterial carbon dioxide tension ranged from 30 to 49 mm Hg; only two patients were hypercapnic. Mean arterial oxygen tensions were not significantly different among the three groups, and there were no significant correlations between forced expiratory volume in one second or FVC and arterial carbon dioxide tension or carbon dioxide production. CONCLUSION: Low values of FVC were associated with increased respiratory rate and decreased tidal volume; this pattern of breathing mimics external elastic loading, suggesting that mechanoreceptors may contribute to the rapid and shallow pattern of breathing in interstitial lung disease. Hypercapnia seems to be rare in interstitial lung disease even when functional impairment is severe and tidal volume is small. The increased respiratory rate is important in maintaining adequate ventilation. In the face of a severe restrictive defect carbon dioxide production did not increase, which also contributed to the maintenance of eucapnia.